Development of integrated information systems in management - Grochowska, Agnieszka; Szaniawska, Agnieszka (Management and Administration Journal, 2023)
Companies that want to actively participate in the space of business connected with internet, will be forced to function in integrated structure, both from business and technological point of view. Currently, the ERP II system is the most developed form that allows that kind of relationship. However, the basis of this system are earlier models. The following article presents the development of integrated information system of management.